Assessment of treatment interruption among pulmonary tuberculosis patients: A cross-sectional study - Satya Bhgath Gorityala; Uday Venkat Mateti; Venkateswarlu Konuru; Srinivas Martha (Journal of Pharmacy and Bioallied Sciences, 2015)
Background: Multi-drug resistant tuberculosis (TB) is a rising peril of the TB control in India caused mostly by incomplete treatment. Aim: The aim was to assess the treatment interruption among pulmonary TB (PTB) patients. Materials and Methods: A cross-sectional study was carried out for a period of 9 months among PTB patients. Patients admitted with active pulmonary Koch′s and history of anti-TB treatment (ATT) for 1-month or more from any source and who returns to treatment after not taking ATT consecutively for 2 months or more were included in the study. The data were collected from the patients or their caretakers to obtain the source of treatment given previously before default, number of treatment interruptions, phase and reasons for treatment interruption treatment. Results: A total of 107 defaulters were identified during the study period. In the present study, 62.6% of the patients interrupted treatment only once, 55.34% of the patient′s early continuation (3-4 months) treatment, and 47.66% of the patient′s only one reason for the treatment interruptions during the course of the treatment. The most common reason for the treatment interruptions were felt well with TB treatment (29.53%) followed by side effects (16.06%), lack of money (8.29%), and other reasons. Conclusion: The study revealed that most of the defaulters were in the age group between 35 and 60 years, male gender, illiterates, daily wage labor, and married. The treatment interruptions were minimized by putting the efforts to improve direct supervision; pretreatment counseling and retrieve treatment interrupters were recommended.